DIFFERENTIAL SIGNS OF PRESUPPOSITION AND SUBTEXT’S (European Journal of Interdisciplinary Research and Development, 2025)
Presupposition and tagmanship are important concepts of pragmatic linguistics in Uzbek linguistics, and their differential signs play a key role in analyzing the hidden meaning of a sentence. In this article, the specific features and differential signs of the phenomenon of presupposition and tagmanship are studied and illustrated with examples.